Validating the Influence of School Learning Environment on Students’ Academic Performance in Selected Universities in Central Uganda - Lwanga, Kayizzi Peter; Peter, Ongodia Simon; Chryesostom, Ssekamwa John (International Journal of Learning and Development, 2024)
The global demand for higher education has been steadily increasing, leading to a rise in student numbers. This surge in enrollment has significant implications for students' learning environment, including factors such as class size and the availability of lecturers. The study was purposely to validate if the learning environment influences students’ academic performance in universities in Central Uganda. The study used 381 final-year undergraduates and 19 lecturers from Nkumba University and Kyambogo University, using a convergent parallel mixed methods research design. The study took both a subjective and objective epistemological stance. Data were collected using a five-point Likert scale structured questionnaire, interview guides, and findings corroborated with a documentary review. The correlation analysis revealed a positive and significant relationship between students’ learning environment and academic performance in the selected universities in Central Uganda (r=.457, p=.000<0.05), and regression analysis showed that all the constructs of students’ learning environment explain 26.7% of the variation in students’ academic performance (R²=0.267). Findings from the study may direct evidence-based policy reform in Uganda’s higher education. The limitations of the study included the selection of a small sample of only two universities which cannot be generalized to all universities in Uganda. The study recommends that policymakers and university management focus on improving the learning environment in universities in Central Uganda.